Head and neck cancer therapy-related oral manifestation management in the COVID-19 pandemic: a critical review - Rafael Resende de MIRANDA; Camila de Carvalho Almança LOPES; Nathália Maria Afonso Silveira FRANCO; Luana Cardoso CABRAL; Paulo Cézar SIMAMOTO JÚNIOR; Veridiana Resende NOVAIS (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract With the onset of the new coronavirus disease (COVID-19) pandemic, the dental treatment of patients at risk of infection has become quite challenging. In view of this, patients with head and neck cancer may present with oral complications due to anticancer therapy, making dental assistance necessary. Thus, the objective of the study was to review the literature and critically discuss important concerns about the treatment of patients with head and neck cancer during the COVID-19 pandemic. Because dental professionals are in close contact with the main viral transmission routes, this study presents recommendations for management and protection during clinical dental care. The main characteristics and transmission routes of COVID-19 are also discussed. Dental professionals should control pain and the side effects of antineoplastic treatment and use preventive measures for infection control. During this pandemic, patients with head and neck cancer should not undergo elective procedures, even if they do not have symptoms or a history of COVID-19; therefore, in asymptomatic or painless cases, only preventive actions are recommended. In symptomatic or painful cases, precautions for safe interventional treatments must be implemented by following the hygiene measures recommended by health agencies and using personal protective equipment. During health crises, new protocols emerge for cancer treatment, and professionals must act with greater attention toward biosafety and updated knowledge. It is important to offer adequate individualized treatment based on the recommendations of preventative and interventional treatments so that patients can face this difficult period with optimized quality of life.